Edukasi Literasi Finansial dalam Menjalankan Bisnis UMKM Secara Online di Kalangan Siswa SMA - Maria Suryaningsih; Susi Susilawati; Moch Rizal; Viniyati Maftuchach; Sahrul Ramadhan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This community service aims to provide an understanding of financial literacy and training and guidance related to the use of social media to disseminate their products online to students of Muhammadiyah Wanaraja Garut High School. The problem faced by partners in this programme is the lack of understanding of students of Muhammadiyah Wanaraja Garut High School regarding financial literacy. The method of implementing this activity using the Participatory Action Research (PAR) method is carried out starting from the socialisation stage at the beginning of the service activity, in the form of providing information to partners / communities about community service activities to be carried out, the objectives of the activity, the stages of implementing the activity, and the schedule for implementing the activity based on an agreement between the proposing team and partners, the next stage of training and mentoring and evaluation of activities. The results of the activity showed an increase in the literacy knowledge of students of Muhammadiyah Wanaraja Garut High School (SMA) related to financial literacy before and after training.